Videolaryngoscopy vs. fibreoptic bronchoscopy for awake tracheal intubation: a systematic review and meta‐analysis. (17th April 2018) - Alhomary, M.; Ramadan, E.; Curran, E.; Walsh, S. R.
Summary: Awake fibreoptic intubation is often considered the technique of choice when a difficult airway is anticipated. However, videolaryngoscopes are being used more commonly. We searched the current literature and performed a meta‐analysis to compare the use of videolaryngoscopy and fibreoptic bronchoscopy for awake tracheal intubation. Our primary outcome was the time needed to intubate the patient's trachea. Secondary outcomes included: failed intubation; the rate of successful intubation at the first attempt; patient‐reported satisfaction with the technique; and any complications resulting from intubation. Eight studies examining 429 patients were included in this review. The intubation time was shorter when videolaryngoscopy was used instead of fibreoptic bronchoscopy (seven trials, 408 participants, mean difference (95%CI) −45.7 (−66.0 to −25.4) s, p < 0.0001, low‐quality evidence). There was no significant difference between the two techniques in the failure rate (six studies, 355 participants, risk ratio (95%CI) 1.01 (0.24–4.35), p = 0.99, low‐quality evidence) or the first‐attempt success rate (six studies, 391 participants, risk ratio (95%CI) 1.01 (0.95–1.06), p = 0.8, moderate quality evidence). The level of patient satisfaction was similar between both groups. No difference was found in two reported adverse events: hoarseness/sore throat (three studies, 167 participants, risk ratio (95%CI) 1.07 (0.62–1.85), p = 0.81, low‐quality evidence), and low oxygen saturation (five studies, 337 participants, risk ratio (95%CI) 0.49 (0.22–1.12), p = 0.09, low‐quality evidence). In summary, videolaryngoscopy for awake tracheal intubation is associated with a shorter intubation time. It also seems to have a success rate and safety profile comparable to fibreoptic bronchoscopy.